VD_FINDINFO HC / 2020 / 595 vom 9. Oktober 2020 - VD Tribunal cantonal (2020)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, IMPÔT | 173 CC, 271 let. a CPC (CH), 272 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 317 CPC (CH)